2012
DOI: 10.1152/ajpendo.00053.2012
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrin attenuates obesity-associated inflammation and insulin resistance in high-fat-fed mice

Abstract: -The aim of this study was to investigate whether treatment with tributyrin (Tb; a butyrate prodrug) results in protection against diet-induced obesity and associated insulin resistance. C57BL/6 male mice fed a standard chow or high-fat diet were treated with Tb (2 g/kg body wt, 10 wk) and evaluated for glucose homeostasis, plasma lipid profile, and inflammatory status. Tb protected mice against obesity and obesityassociated insulin resistance and dyslipidemia without food consumption being affected. Tb attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 54 publications
12
90
1
4
Order By: Relevance
“…A low concentration of butyrate was reported to inhibit the proliferation of T-lymphocytes, and to induce apoptosis in activated T-lymphocytes, but not primary macrophages 41) . In the adipose tissue of obese mice, butyrate decreased infiltration by leukocytes 24) . Therefore, butyrate might contribute to the attenuation of inflammation in obese adipose tissues via the induction of T-cell apoptosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A low concentration of butyrate was reported to inhibit the proliferation of T-lymphocytes, and to induce apoptosis in activated T-lymphocytes, but not primary macrophages 41) . In the adipose tissue of obese mice, butyrate decreased infiltration by leukocytes 24) . Therefore, butyrate might contribute to the attenuation of inflammation in obese adipose tissues via the induction of T-cell apoptosis.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, Gao et al reported improved insulin resistance by long-term ingestion of sodium butyrate in obese mice 23) . Vinolo et al also reported that oral administration of tributyrin improved obesity-associated inflammation in mice fed a high-fat diet 24) ; however, the effect of butyrate on the mutual inflammatory response in adipocytes and macrophages has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…15 SCFA treatment has ameliorated colitis, airway disease, and metabolic syndrome in diet-induced obese mice. [16][17][18] So far, researchers suggested that SCFAs may operate in two manners: by binding G-protein membrane receptors (GPR41 and GPR43), 19,20 or by entering cells directly through transporter channels in the cellular membrane and working as histone deacetylase (HDAC) inhibitors. Thus, they could act by modulating epigenetic processes.…”
mentioning
confidence: 99%
“…table 1S; for all online suppl. material, see www.karger.com/doi/10.1159/000381777) [31,32]. For both diets, the lard:soybean oil ratio was 9:1.…”
Section: Methodsmentioning
confidence: 99%